Types of screening tools used to identify potential inappropriate medication in the geriatric - Abdullah, Marwah Y.; Alomari, Majed M.; AlNihab, Ali N.; Alshaikh, Maha S.; Alzahrani, Maryam A.; Al-Shehab, Ali H.; Alghafli, Munthir H.; Shaban, Ayat E.; Bajaba, Majed A.; Yateem, Samia S. Al; Alseraihi, Ahmad A. (International Journal Of Community Medicine And Public Health, 2022)
Inappropriate intake of medications can increase the risk of many morbidities and mortality among the geriatric population. Therefore, assessment of drug underuse, overuse, and inappropriate use has been an area of interest across the different investigations, and according to which, different screening tools were developed to identify these problems and enhance the quality of care to these patients. In the present study, we aim comprehensively discuss the different types of currently reported screening tools that can identify potentially inappropriate medication in the geriatric population. Studies show that assess, review, minimize, optimize, reassess (ARMOR), and medication appropriateness index (MAI) tools are the most commonly reported for this purpose to appropriately evaluate drug administration practices. However, they are time-consuming and need adequately trained personnel, which might not be available within the different settings. Accordingly, we suggest that more than one tool should be used, as we have reviewed all the advantages and disadvantages of the modality within the current study, to adequately facilitate and make the process of evaluation easy and enhance the quality of care for the geriatric population.